Evaluation of occupational and medical dose on interventional cardiology procedures by Monte Carlo method - Santos, W. S.; Júnior, A. B. C.; Maia, A. F. (Scientia Plena, 2012)
Interventional cardiology consists on a set of medical procedures which are mainly focused on diagnosing and treating patients who suffer cardiovascular diseases. Even though the usage of X-ray is justified on this case, it is greatly advised to evaluate the dose which professionals and patients will be exposed due to the fact that the complexity and length of the procedures often require high doses. The objective of this work is to estimate the radiation dose on both a patient and a physician through conversion coefficient (CCs) of effective dose (E) and equivalent dose (H) during a coronary angiography examination.The dose CCs was estimated using the Visual Monte Carlo code (VMC) and a pair of simulators anthropomorphic voxel (Female Adult VoXel). The CCs were normalized in terms of kerma-area product (KAP). As expected, for all situations studied, the patient in anteroposterior projection (AP) obtained the highest conversion coefficient of equivalent dose and effective dose.